Mangosteen Peel Extract vs Tetracycline Gel in Treatment of Periodontal Abscess in Type-2 Diabetes – A Randomized Clinical Trial - Ramesh, KSV; Joshna, Itha; Penmetsa, Gautami S; Sruthima, Gottumukkala NVS; Kumar, Pasupuleti Mohan; Anusha, Boddeda; Valli, Sathya (UI Scholars Hub, 2024)
Herbal products are gaining popularity due to their diverse biological action and safety. Mangosteen peel extract has antibacterial and anti-inflammatory properties and can be used to treat periodontal diseases. Objective: To compare the efficacy of mangosteen peel extract and tetracycline gel as an adjunct to non-surgical management of periodontal abscess in type-II diabetes patients. Methods: This was a double blinded, randomized clinical trial included 20 Patients with Type-II diabetes. Both test and control groups received NSPT followed by adjunctive local application of mangosteen peel extract and tetracycline gel. Clinical parameters i.e., Probing depth (PPD), Clinical attachment level (CAL), Bleeding Index (BI) and Landry’s healing index (HI) were evaluated at base line and 1 month. Results: In intra and intergroup analysis, both the test and control groups had a better reduction in PPD, BI and CAL with a statistical significance. However, there was no statistical significance between the groups in healing index and showed no change in patient perception in both the groups. Conclusion: 4% mangosteen gel has significantly reduced the BI and PPD with increased CAL and acceptable subjective perception with no recurrence of periodontal abscess over the traditionally used tetracycline gel.